2023
DOI: 10.1055/a-2008-2495
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Preterm Birth in Pregnancies Complicated by Nonimmune Hydrops Fetalis

Abstract: Objective: Nonimmune hydrops fetalis (NIHF) is associated with poor perinatal outcomes including preterm birth (PTB). However, the frequency and causes of PTB in this population are not well understood. We hypothesized that NIHF frequently results in PTB due to medically indicated delivery for fetal distress. Study Design: This was a secondary analysis of a prospectively enrolled cohort of pregnancies with NIHF that underwent exome sequencing if standard testing was non-diagnostic. The primary outcome was fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…Our stillbirth rate of 52% compared with 14%–31% in larger cohorts of prenatal NIHF 2,18 may be due to our strict NIHF definition and exclusion of non‐genetic etiologies. Our finding that most (73%) NIHF live births occurred preterm is consistent with published literature 2,8 . Our predominance of indicated preterm delivery (82%) for fetal indications (78%) in NIHF pregnancies is concordant with a recent study where 63% of preterm deliveries in NIHF pregnancies were indicated, 70% for fetal indications 8 .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our stillbirth rate of 52% compared with 14%–31% in larger cohorts of prenatal NIHF 2,18 may be due to our strict NIHF definition and exclusion of non‐genetic etiologies. Our finding that most (73%) NIHF live births occurred preterm is consistent with published literature 2,8 . Our predominance of indicated preterm delivery (82%) for fetal indications (78%) in NIHF pregnancies is concordant with a recent study where 63% of preterm deliveries in NIHF pregnancies were indicated, 70% for fetal indications 8 .…”
Section: Discussionsupporting
confidence: 92%
“…Our finding that most (73%) NIHF live births occurred preterm is consistent with published literature 2,8 . Our predominance of indicated preterm delivery (82%) for fetal indications (78%) in NIHF pregnancies is concordant with a recent study where 63% of preterm deliveries in NIHF pregnancies were indicated, 70% for fetal indications 8 . Possible explanations include increased surveillance and advances in neonatal care 8 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations